Decoupled Pi Controllers Based on Pulse-Frequency Modulation for Current Sharing in Multi-Phase Llc Resonant Converters - Rojas-Lobos, F (Institute of Electrical and Electronics Engineers Inc., 2021)
The LLC series resonant converter has emerged as a solution to applications requiring power conversion with isolation, reduced volume and high efficiency, such as PV systems and EV chargers. However, the LLC resonant converter is limited in power, so it requires a multi-phase configuration in order to provide higher currents. This configuration connects the outputs of two or more LLC converters in parallel, increasing the output current but introducing imbalance and circulating currents due to the mismatch and tolerance values of components in each resonant tank. This paper proposes a simple PI control scheme to compensate the current imbalance and eliminate circulating currents generated when several LLC resonant converters are connected in parallel. Unlike reported current sharing methods, the proposed control scheme is based on multiple current control loops operating independently, using the switching frequency of each parallel-connected unit as a degree of freedom of the overall converter. The proposed control scheme has been successfully validated under simulations and experimental assessment, implementing two resonant tanks with ±5% tolerance of parameters, providing excellent steady-state and transient performance. © 2013 IEEE.